2003
DOI: 10.1007/s00464-002-9159-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopically assisted colectomy and ileoanal pouch procedure with and without protective ileostomy

Abstract: Laparoscopically assisted restorative proctocolectomy is technically feasible; an increased BMI is a relevant risk factor for failure. The minimally invasive approach probably does not reduce the need for a protective ileostomy in selected patients. The selection criteria for the addition or omission of a protective ileostomy in minimally invasive restorative proctocolectomy remain to be clearly defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
0
11

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 27 publications
8
71
0
11
Order By: Relevance
“…The possible advantages of a laparoscopic approach are a quicker recovery, potentially lower incidence of small bowel obstruction and other morbidities, and superior cosmetic results. There are now several reports assessing the feasibility and outcomes after a LIPAA in small series of patients [20,21,22,23,24]. The operation usually involves complete laparoscopic mobilization of the colon with intracorporeal vascular ligation, followed by exteriorization of the bowel through a Pfannenstiel incision.…”
Section: Ulcerative Colitismentioning
confidence: 99%
See 1 more Smart Citation
“…The possible advantages of a laparoscopic approach are a quicker recovery, potentially lower incidence of small bowel obstruction and other morbidities, and superior cosmetic results. There are now several reports assessing the feasibility and outcomes after a LIPAA in small series of patients [20,21,22,23,24]. The operation usually involves complete laparoscopic mobilization of the colon with intracorporeal vascular ligation, followed by exteriorization of the bowel through a Pfannenstiel incision.…”
Section: Ulcerative Colitismentioning
confidence: 99%
“…The largest reported experience for LIPAA comes from the University of Heidelberg in Germany [20]. Fifty-nine patients with UC and familial adenomatous polyposis were included in a prospective cohort study.…”
Section: Ulcerative Colitismentioning
confidence: 99%
“…The technical feasibility of this approach has been shown in several series in specialized centers [28,29]. However, there is controversy in the literature on the actual benefit of minimal invasive techniques for such extensive colorectal surgery.…”
Section: Minimally Invasive Techniquesmentioning
confidence: 99%
“…Schmitt et al [28] compared duration of ileus and of hospitalization in 22 patients who underwent laparoscopic-assisted colectomy and 20 age, gender, and diagnosis-matched controls who underwent standard colectomy and they found that neither the length of time for ileus resolution nor the length of hospitalization were reduced in the laparoscopic group concluding that Lap-IPAA failed to provide any of the theoretical advantages described for other laparoscopic procedures. Other series of patients with MUC or FAP treated with laparoscopic TPC + IPAA are listed in table 1 [17,18,[29][30][31][32][33][34] .…”
Section: Laparoscopic Surgery For Ulcerative Colitis and Familial Adementioning
confidence: 99%
“…In 1976, Parks and Nicholls [15] described the technique of ileal reservoir-anal anastomosis after total proctocolectomy in 8 patients with MUC, obtaining satisfactory results in 4 out of 5 patients available to follow-up by the time of publication. During the last 30 years, restorative proctocolectomy with ileal pouchanal anastomosis (IPAA) has become the standard surgical treatment for patients with MUC and FAP [11][12][13][16][17][18][19][20][21] and several modifications to the original technique have been advocated including changes to the shape of the pouch itself [12,13] . In the original technique, a transanal mucosectomy followed by a pouch-anal hand-sewn anastomosis was performed [12,15] .…”
Section: Laparoscopic Surgery For Ulcerative Colitis and Familial Adementioning
confidence: 99%